The Role of Augmented Reality-Based Learning in Enhancing Students' Motivation and Learning Outcomes - Nugraheni Agustyaningsih; Nurita Putranti; Rika Kartika (Journal of Mandalika Social Science, 2026)
The increasing integration of digital technologies in education has encouraged the adoption of Augmented Reality (AR) as an innovative learning approach. This study aims to examine the role of AR-based learning in enhancing students’ motivation and learning outcomes through a systematic review of existing literature. A qualitative approach using a Systematic Literature Review (SLR) design was employed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A total of 35 relevant studies published between 2017 and 2026 were selected and analyzed, including empirical studies, systematic reviews, meta-analyses, bibliometric analyses, and review articles. The findings indicate that AR-based learning positively influences students’ motivation by increasing engagement, interest, satisfaction, enjoyment, and participation in learning activities. In addition, AR contributes to improved learning outcomes, particularly in academic achievement, conceptual understanding, knowledge retention, and problem-solving skills. The review also identifies several challenges affecting the implementation of AR in educational settings, including technological limitations, infrastructure constraints, teacher readiness, implementation costs, and accessibility issues. Furthermore, recent research trends highlight the growing application of AR across various educational disciplines and the increasing integration of AR with emerging technologies. This study concludes that AR-based learning has significant potential to support both motivational and cognitive aspects of learning when implemented with appropriate pedagogical and technological support. The findings provide valuable insights for educators, researchers, and policymakers seeking to enhance educational practices through innovative digital learning technologies.